Effect of humidity on egg hatchability and reproductive biology of the bamboo borer (Dinoderus minutus Fabricius) - Ahmad Razi, Norhisham; Abood, Faizah; Muhamad Awang, Rita; Hakeem, Khalid Rehman (SpringerOpen, 2013)
Wood products are highly exposed to infestation by powder post beetles. Dinoderus minutus (bamboo borer) is a wood boring beetle that seriously damage dried bamboo and finished bamboo products. Management of D. minutus using pesticides showed negative effects on environment despite being very costly. By understanding influence of natural climatic conditions on their reproductive behaviour, could help us to develop a cost effective and environmental friendly strategy to cope up with this problem. In the present study, reproductive parameters and egg development of the bamboo borer were determined at 20%, 40%, 56%, 75% and 85% r.h. levels at constant temperature of 30° ± 2°C with 8 L-16D photoregime. From the results, eclosion to first instar larva was recorded at all relative humidities tested. The lowest shortest percentage of hatchability was recorded at 20% and 85% relative humidity with a mean incubation period of 4.63 ± 0.25 and 10.43 ± 0.32 days, respectively. It was noted that pre-ovipositional period decreased from 14.20 ± 0.49 to 7.20 ± 0.31 days as relative humidity increased from 20% to 75% and slightly increased to 8.00 ± 0.37 days at 85% relative humidity. We conclude that female beetles may have a particular hygropreference in oviposition as total egg production increased with increasing relative humidity.